MARKETING MIX IN LOCAL MINIMARKETS CREATES PURCHASE DECISIONS AND HAS IMPLICATIONS FOR CUSTOMER SATISFACTION - Syamsul Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Purpose – This study examined the influence of the marketing mix, consisting of product, price, promotion, and place, on purchase decisions and customer satisfaction and the mediating effect of purchase decisions. Methodology – The sample consisted of 250 customers at local minimarkets in Lhokseumawe City taken using Purposive sampling method. Primary data were collected using a structured questionnaire and were tested for validity and reliability. The analysis tool was path analysis with the SEM (Structural Equation Modelling) method using AMOS. Findings – The results indicated that each element of the marketing mix, namely product, price, promotion, and place, positively and significantly influenced purchase decisions and customer satisfaction. Furthermore, the purchase decision directly affected customer satisfaction and mediated the relationship between the product mix elements (product, price, promotion, and place) and customer satisfaction. Originality – This study examined the influence of marketing mix elements on purchase decisions and customer satisfaction. Besides, this study also seeks to test the mediating effect of customer purchase decisions at local minimarkets in Lhokseumawe City.